2016
DOI: 10.1155/2016/2071945
|View full text |Cite
|
Sign up to set email alerts
|

Wear Scar Similarities between Retrieved and Simulator-Tested Polyethylene TKR Components: An Artificial Neural Network Approach

Abstract: The aim of this study was to determine how representative wear scars of simulator-tested polyethylene (PE) inserts compare with retrieved PE inserts from total knee replacement (TKR). By means of a nonparametric self-organizing feature map (SOFM), wear scar images of 21 postmortem- and 54 revision-retrieved components were compared with six simulator-tested components that were tested either in displacement or in load control according to ISO protocols. The SOFM network was then trained with the wear scar imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
2
7
0
Order By: Relevance
“…However, the mean lifetime of the analyzed retrievals is comparable with the mean running times of the analyzed inserts from the simulator tests, according to Battenberg et al [ 31 ]. Studies on retrievals with average lifetimes comparable with those used in the present study are reported in the literature [ 20 , 21 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mean lifetime of the analyzed retrievals is comparable with the mean running times of the analyzed inserts from the simulator tests, according to Battenberg et al [ 31 ]. Studies on retrievals with average lifetimes comparable with those used in the present study are reported in the literature [ 20 , 21 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For total hip replacement, it is stated that standard wear simulator tests cannot predict the in vivo situation in an exact manner for the entire time of the implantation [ 11 , 17 , 18 ]. Additionally, for total knee replacement (TKR), some studies of retrievals and standard wear testing showed a significant discrepancy in wear data [ 19 , 20 , 21 , 22 , 23 ]. Previous studies had focused on implant malpositioning, overloading, and reasons for enhanced wear of TKR [ 21 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies have investigated the difference in wear due to prosthesis design, it is unknown how using inputs for wear testing from populations of TKR patients implanted with different prostheses will affect the outcome of wear tests. However since wear tested simulator components continue to not be representative of wear measured on retrieved TKRs [35,36], work should continue towards defining accurate wear simulation inputs generalizable to multiple TKR patient cohorts who participate in a variety of daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-validation procedure was repeated until each patient was used as the test subject in his or her corresponding wear group. ANN can be considered a nonlinear regression model that can model the relationship between the independent variables (predictors) and dependent variable in an analogous fashion to linear regression [4][5][6][7]38]. The most-featured difference between linear regression and ANN is that the latter splits a complex nonlinear relationship into several piecewise approximations, where each approximation is generated as a nonlinear function of predictors (instead of a simple linear combination of predictors as in linear regression).…”
Section: Wear Predictive Modelmentioning
confidence: 99%